Utopia in the anthropocene a change plan for a sustainable and equitable world - Harvey, Michael 1952- (Routledge, 2019)
The burning platform -- The crisis of the anthropocene : change mismanaged -- The growthist world system -- The goals and values behind our "mad" world plan - and who's behind it -- What keeps the system going : the economics, business and politics of growthism -- The wealth fallacy : the psychology and culture of growthism -- The worst case scenario : dystopia in the anthropocene -- The change plan : 12 steps towards a people-planet utopia -- Define the utopian vision (the sewp model) -- Set goals and clarify values -- Support an ecological revolution in economics -- Put wellbeing and community first -- Build a circular democracy (and champion the transvaluation of politics) -- Embrace utopian internationalism -- Help to grow post-growth enterprises -- Manage yourself to utopia (by democratising leadership and other organizational practices) -- Put psychology to work on transforming our values -- Learn from the utopian imagination -- Think and act like a utopian -- Take heart from history
Includes bibliographical references and index
Keywords: Humanökologie; Nachhaltigkeit; Anthropozän; Nature / Effect of human beings on; Human ecology / Economic aspects; Human ecology / Political aspects; Sustainability